2008
DOI: 10.1111/j.1538-7836.2008.03002.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health‐related quality of life during the 2 years following deep vein thrombosis

Abstract: Summary. Background/objectives: We prospectively measured change in quality of life (QOL) during the 2 years after a diagnosis of deep vein thrombosis (DVT) and evaluated determinants of QOL, including development of the postthrombotic syndrome (PTS). Patients/methods: Consecutive patients with acute DVT were recruited from 2001 to 2004 at eight hospitals in Canada. At study visits at baseline, and 1, 4, 8, 12 and 24 months, clinical data were collected, standardized PTS assessments were performed, and QOL que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
379
2
19

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(418 citation statements)
references
References 30 publications
18
379
2
19
Order By: Relevance
“…[4] If not fatal, untreated venous thromboembolism (VTE) may have serious consequences such as risk of recurrent VTE, [1] postthrombotic syndrome, [1] chronic thromboembolic pulmonary hypertension [5] and reduced quality of life. [6] The prevalence of VTE and the use of pharmacological thromboprophylaxis in total hip replacement (THR), total knee replacement (TKR) and hip fractures have been well documented in published literature and in clinical trials. [1,[7][8][9][10] Although there is potentially an increased risk of VTE in foot and ankle surgery, the incidence of VTE is poorly understood.…”
Section: Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] If not fatal, untreated venous thromboembolism (VTE) may have serious consequences such as risk of recurrent VTE, [1] postthrombotic syndrome, [1] chronic thromboembolic pulmonary hypertension [5] and reduced quality of life. [6] The prevalence of VTE and the use of pharmacological thromboprophylaxis in total hip replacement (THR), total knee replacement (TKR) and hip fractures have been well documented in published literature and in clinical trials. [1,[7][8][9][10] Although there is potentially an increased risk of VTE in foot and ankle surgery, the incidence of VTE is poorly understood.…”
Section: Researchmentioning
confidence: 99%
“…Although the majority of recent studies do not advocate the routine use of chemoprophylaxis in foot and ankle surgery, [6,12,13,21,22,25,27,30,33,[38][39][40] several authors recommend its use in patients with identifiable specific clinical risk factors. [6,[8][9][10][11][12][13][14][15][16][17][18][19][20]26,37,41] A difficulty of long-term follow-up of patients is that many DVT events occur several weeks or longer after discharge.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In fact, 2 years post-DVT, the development of PTS remained the primary determinant of health-related QOL scores. 30 Given this significant risk of PTS in the cancer population and potentially adverse effects, consideration for aggressive treatment should be given to all DVT patients, including those with cancer. Evaluation and treatment planning should be centered on QOL and the potential for improvement.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…A number of various family and twin studies have revealed that genetic factors account for more than 60% of the risk for developing DVT (26,27). Regardless of ideal traditional treatment strategies with anticoagulants, a post-thrombotic syndrome often develops in one in four patients within a year while DVT recurs in one-third of patients within five years (28,29).…”
Section: Discussionmentioning
confidence: 99%